Gender, population, and development - Krishna Raj, Maithreyi; Sudarshan, Ratna M.; Shariff, Abusaleh (Delhi Oxford University Press, 1998)
Collection of papers presented at a conference held at Delhi in January 1996.
PI-8439 donated by Lindy Williams.
Keywords: Birth control -- India -- Congresses; Women in development -- India -- Congresses; Women -- Social conditions -- India -- Congresses; Sex role -- India; Women -- Employment -- India; India -- Population policy -- Congresses; India -- Economic conditions